2008
DOI: 10.1007/s11010-008-9739-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid peroxidation and antioxidant status in pregnancy with preeclampsia

Abstract: The present study was intended to appraise the oxidant and antioxidant status in preeclampsia women. Seventy-seven preeclampsia women with severe variety having average B.P. of 170/140 mmHg with proteinuria; 47 preeclampsia women with mild variety having average B.P. of 138/100 mmHg were compared to 56 healthy pregnant women and 15 non-pregnant women for oxidant and antioxidant status. Lipid peroxidation was assessed by measuring malondialdehyde (MDA), and antioxidant status was assessed by measuring antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 30 publications
8
48
1
1
Order By: Relevance
“…33 Moreover, antioxidants also prevent lipid peroxidation by free radical inactivation. 34 Our study showed a significantly lower level of vitamin A (p = 0.02) in acne patients in comparison with controls, but the difference between vitamin E was not significant. According to an earlier study, retinoids (a chemical form of vitamin A) was used to treat acne vulgaris which suggests that vitamin A deficiency can be a causative factor of this disease which we found in our study as well.…”
Section: Resultscontrasting
confidence: 62%
“…33 Moreover, antioxidants also prevent lipid peroxidation by free radical inactivation. 34 Our study showed a significantly lower level of vitamin A (p = 0.02) in acne patients in comparison with controls, but the difference between vitamin E was not significant. According to an earlier study, retinoids (a chemical form of vitamin A) was used to treat acne vulgaris which suggests that vitamin A deficiency can be a causative factor of this disease which we found in our study as well.…”
Section: Resultscontrasting
confidence: 62%
“…Their elevation may be an adaptive response to counter the effect of increased oxidative stress. Reduced glutathione was found to be decreased in preeclamptic females in studies at Turkey and study by Kaur G et al [10] in India. The latter study also showed significant elevation in Vitamin E levels as compared to normal pregnancy.…”
Section: Discussion and Analysismentioning
confidence: 82%
“…15 The present study found that catalase was significantly lower in the PE group than in the HP and NP groups, an observation compatible with the results of previous investigations. 29,30 Antioxidant nutrient levels can be manipulated simply by dietary or pharmacological supplements. 9 The importance of vitamin E and β-carotene in preventing free radical damage is well known and their levels have been reported to be significantly decreased in pre-eclampsia.…”
Section: Discussionmentioning
confidence: 99%